Classroom Gems : Games Ideas and Activit: Games, Ideas and Activities for Primary Music - Minto, Donna (New Dehli Pearson, 2014)
Description Games, Ideas and Activities for Primary Music is a handy tool for Primary Music teachers it is packed full of simple activities for your classroom and is organised by skill - singing, rhythm, playing, listening.? Activities can be easily adapted to suit different classes or topics and help you to feel more confident teaching Music. Prior musical knowledge is not necessary to use these activities, and a glossary of music terminology is included.? Cross-curricular links inspire creativity across the primary curriculum and brighten up your classroom!
Include Illustrations
Keywords: Teaching Music